COVID-19: looking beyond the peak. Challenges and tips for radiologists in follow-up of a novel patient cohort. Issue 1 (January 2021) - McStay, R.; Johnstone, A.; Hare, S.S.; Jacob, J.; Nair, A.; Rodrigues, J.C.L.; Edey, A.; Robinson, G.
Abstract : As the coronavirus pandemic evolves, the focus of radiology departments has begun to change. The acute phase of imaging a new disease entity whilst rationalising radiology services in the face of lockdown has passed. Radiologists are now becoming familiar with the complications of COVID-19, particularly the lung parenchymal and pulmonary vascular sequelae and are considering the impact follow-up imaging may have on departments already struggling with a backlog of suspended imaging in the face of reduced capacity. This review from the British Society of Thoracic Imaging explores both the thoracic and extra-thoracic complications of COVID-19, recognising the importance of a holistic approach to patient follow-up. The British Thoracic Society guidelines for respiratory follow-up of COVID-19 will be discussed, together with newly developed reporting templates, which aim to provide consistency for clinicians as well as an opportunity for longer-term data collection.